КОМПЕТЕНТНІСНІЙ ПІДХІД - ЯК ЗАСІБ РОЗВИТКУ СУЧАСНОЇ ЕКОНОМІЧНОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2007)
In the article, the essence o f notion is considered “competence”, value of competence of specialists economic type, new approaches in relation to forming of competence of specialists in higher educational establishments.